1993
DOI: 10.1091/mbc.4.9.963
|View full text |Cite
|
Sign up to set email alerts
|

Heterokaryon myotubes with normal mouse and Duchenne nuclei exhibit sarcolemmal dystrophin staining and efficient intracellular free calcium control.

Abstract: Duchenne and mdx muscle tissues lack dystrophin where it normally interacts with glycoproteins in the sarcolemma. Intracellular free calcium ([Ca2+]i) is elevated in Duchenne and mdx myotubes and is correlated with abnormally active calcium-specific leak channels in dystrophic myotubes. We fused Duchenne human and normal mouse myoblasts and identified heterokaryon myotubes by Hoechst 33342 staining to measure the degree to which dystrophin introduced by normal nuclei could incorporate throughout the myotube at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
8
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
4
8
0
Order By: Relevance
“…We thus of the same cultures that were not transfected (Figure 2). Restoration of dystrophin expression therefore improved extend our earlier results from myoblast fusion and transgenic mice, 24,25 and show that liposome-mediated transintracellular calcium regulation in originally dystrophic muscle cells.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…We thus of the same cultures that were not transfected (Figure 2). Restoration of dystrophin expression therefore improved extend our earlier results from myoblast fusion and transgenic mice, 24,25 and show that liposome-mediated transintracellular calcium regulation in originally dystrophic muscle cells.…”
supporting
confidence: 80%
“…As previously reported in studies using the extrapolated reversal potential were both similar to previously reported values. 12,16 fura-2, 12,13,16,17,24,25 the resting [Ca 2+ ] i here is significantly higher in mdx myotubes than that in age-matched normal…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Primary myotube cultures were prepared by isolating satellite cells from hind-limb muscles of 10-week-old adult mice and culturing as previously described (DiMario and Strohman, 1988;Denetclaw et al, 1993). Briefly, myoblasts were proliferated for 5-6 d in Ham's F10 medium with 20% FBS and 2% chick embryo extract.…”
Section: Muscle Cells and Culturementioning
confidence: 99%
“…In the absence of dystrophin, one observes greater total muscle calcium (Bertorini et al, 1982;Dunn and Radda, 1991), as well as a significant elevation in intracellular free calcium concentrations ([Ca21]i) in isolated myofibers (Lopez et al, 1987;Turner et al, 1988) and ©) 1994 by The American Society for Cell Biology cultured myotubes (Mongini et al, 1988;Sarabia and Klip, 1989;Fong et al, 1990;Turner et al, 1991Turner et al, , 1993Denetclaw et al, 1993;Bakker et al, 1993), although others have not observed differences in resting calcium (Gailly et al, 1993;Head, 1993;Pressmar et al, 1994). However, no difference is observed in calcium resequestration rates after stimulation (Turner et al, 1991), indicating that calcium efflux pathways are not impaired in dystrophic cells, and, instead, an influx pathway may be altered.…”
Section: Introductionmentioning
confidence: 99%